Isolation and identification of pathogenic bacteria in edible fish: A case study of rural aquaculture projects feeding livestock manure to fish in Zimbabwe - Sichewo, Petronillah Rudo; Gono, Robert Kudzanayi; Muzondiwa, John; Mungwadzi, Willard (Excellent Publishers, 2022)
Integrated fish farming combines livestock production with fish farming. Animal manure is shed directly into a fish pond as fertilizer and supports the growth of photosynthetic organisms. The use of different kinds of livestock manure in fish production may increase the level of pathogenic bacteria causing a public health risk to the rural community. Bacterial pathogens associated with fish can be transmitted to human beings from the fish used as food or by handling the fish, (biochemical and gram staining reactions). The following human pathogenic bacteria were isolated Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Enterococcus faecalis. All the bacterial species which were isolated from the fish were also present in the initial water samples collected. The isolation of enteric bacteria in fish serves as indicator organisms of faecal contamination and or water pollution. Their presence also represents a potential hazard to humans. The mean bacterial load of the isolates was found to be markedly lower than the recommended public health and standard value of 5.0 x 10 5 CFU/ml which has been adopted by many countries.